A histological study of the skin, hair follicles and moult of the hooded seal (Cystophora cristata [Erxleben, 1777]). Issue 1 (1st January 2018) - Ling, John K.
ABSTRACT: The aims of this study were to (1) provide a general description of the hooded seal's integument; (2) diagnose hair follicle activity stages and develop a chronology for the annual moult within the different sex and age classes; (3) examine the population characteristics of the moult haul-out; and (4) seek possible correlations between these events and the hooded seal's annual cycle. Skin samples were collected from 68 moulting hooded seals out of 868 taken in the Denmark Strait for population studies during June and July 1972. The microstructure of the integument of this species is described. It varies little from what is known from other northern phocids. However, they appear to be one to two "intermediate" guard hair follicles within up to seven underfur follicles; these are smaller than the main guard hair follicle in each hair follicle complex. The hair follicles in the skin of most hooded seals of both sexes and all ages sampled between 21 June and 11 July 1972 were at early to middle stages of activity, suggesting that hair growth starts somewhat earlier than mid-June and ends later than mid-July. It appears that female moult haul-out numbers started to decline about four to five days earlier than the males, but when the haul-out began or ended could not be determined. The brevity, synchronicity and precision of the moult (and breeding season) suggest that its timing is controlled by an environmental factor such as day length at the high northern latitudes inhabited by hooded seals.